Spatial spectrum based blind spectrum sensing for multi-antenna cognitive radio system - Chang LIU; SajjadAli Syed; Rui ZHANG; Si-ying LI; Jie WANG; Ming-lu JIN (Tongxin xuebao)
State-of-the-art sensing methods only exploit three dimensions of the spectrum space:frequency，time and space whereas the angle dimension has not been exploited well enough for opportunistic spectrum access.Motivated by this，the authors apply angle of arrival (AOA) estimation algorithm to spectrum sensing and propose two blind spectrum sensing methods based on spatial spectrum.First is based on the ratio of maximum to minimum delay-sum spatial spectrum; the other is based on the ratio of average to minimum delay-sum spatial spectrum.Taking the advantage of spatial matched filtering，the proposed methods can achieve high probability of detection as well as offer the AOA information for spectrum access，which improve the spectrum efficiency.In addition，utilizing latest random matrix theories (RMT)，this work quantifies the detection threshold and derives the probabilities of detection for the proposed methods in theory.Extensive simulations carried out in Nakagami-m fading channel indicate that the proposed methods outperform the existing blind spectrum sensing methods.